Legacies of the past : memory and trauma in Mexican visual and screen cultures - Thornton, Niamh; Haddu, Miriam, 1971- (Edinburgh University Press, 2020)
Riven with unresolved traumas and appropriated by successive governments, the past haunts spaces in Mexican film and visual culture. These events, without consensus or a singular/unifying narrative, act like spectres haunting the present. To comprehend how they manifest, Legacies of the Past considers how filmmakers and visual artists have found ways of understanding these haunted spaces. With case studies of films like El atentado (2010), Flor en Otomi (2012) and the photography of Dulce Pinzon, this collection analyses the audio-visual representations of several heightened events in Mexican history. The contributors' explorations, imaginings and counter-imaginings bring the past to the foreground, creating new narratives and proposing new histories in order to show the significance of storytelling and narrative for a shared understanding of ourselves.
Keywords: Motion pictures -- Mexico -- History.; Psychic trauma in motion pictures.; Mexico -- In motion pictures.; Mexico -- History.; Cinéma -- Mexique -- Histoire.; Traumatisme psychique au cinéma.; Mexique -- Histoire.; PERFORMING ARTS / Film & Video / History & Criticism; Motion pictures; Psychic trauma in motion pictures; Mexico; Electronic books.; History